Drosophila CAF-1 regulates HP1-mediated epigenetic silencing and pericentric heterochromatin stability. - Huang, H.; Yu, Z.; Zhang, S.; Liang, X.; Chen, J.; Li, C.; Ma, J.; Jiao, R. (Journal of Cell Science, 2010)
Chromatin assembly factor 1 (CAF-1) was initially characterized as a histone deliver in the process of DNA-replication-coupled chromatin assembly in eukaryotic cells. Here, we report that CAF-1 p180, the largest subunit of Drosophila CAF-1, participates in the process of heterochromatin formation and functions to maintain pericentric heterochromatin stability. We provide evidence that Drosophila CAF-1 p180 plays a role in both classes of position effect variegation (PEV) and in the expression of heterochromatic genes. A decrease in the expression of Drosophila CAF-1 p180 leads to a decrease in both H3K9 methylation at pericentric heterochromatin regions and the recruitment of heterochromatin protein 1 (HP1) to the chromocenter of the polytene chromosomes. The artificial targeting of HP1 to a euchromatin location leads to the enrichment of Drosophila CAF-1 p180 at this ectopic heterochromatin, suggesting the mutual recruitment of HP1 and CAF-1 p180. We also show that the spreading of heterochromatin is compromised in flies that have reduced CAF-1 p180. Furthermore, reduced CAF-1 p180 causes a defect in the dynamics of heterochromatic markers in early Drosophila embryos. Together, these findings suggest that Drosophila CAF-1 p180 is an essential factor in the epigenetic control of heterochromatin formation and/or maintenance.